Operationalizing an innovation platform approach for community-based participatory research on conservation agriculture in Burkina Faso - Dabiré, Der; Andrieu, Nadine; Djamen, Patrice; Coulibaly, Kalifa; Posthumus, Helena; Diallo, Amadou Mohamadoun; Medina, Karambiri; Douzet, Jean-Marie; Triomphe, Bernard (Cambridge University Press, 2017)
Numerous innovation platforms have been implemented to encourage the adoption of agricultural innovations and stakeholder interactions within a value chain. Yet little research has been undertaken on the design and implementation of innovation platforms focussing on issues other than market access and aiming to encourage agro-ecological intensification. This is the case for the development of Conservation Agriculture (CA) in West Africa, which due to its complex nature calls for technical, organizational and institutional changes at the level of both production systems and village territories. This article analyses the design and implementation process of platforms in three villages in Burkina Faso aiming to develop CA technical references with local stakeholders, and to renew rules of interaction between stakeholders within a territory. The platforms enabled farmers in the three villages to actively participate in the identification of the cropping systems that were tested and to improve their knowledge and mastery of CA. They furthermore promoted networking among producers and facilitated the development of new rules for crop residue use. The platforms thus appear to be relevant mechanisms, enabling complex innovations to be addressed. Diverse modifications and improvements are discussed that would ensure the sustainability of the platforms and the evolution of their objectives and activities beyond those of the project under which they were launched.